equação de 1 grau : a) 7-2 ( - x -3) = 8 - 5 . ( x - 1) b)8 . (X - 3 ) + 2 . ( 5 - X) = - X C ) 2 . (-2 X + 3) -5 (2 -X ) =3 . (2X +3) ME - AJUDEM POR FAVOR
Respostas
respondido por:
5
a)7 + 2X + 6 = 8 - 5X + 5
2X + 5X = 8 + 5 -7 -6
7X = 0
X = 0/7 = 0
b) 8X -24 + 10 - 2X = - X
7X = 14
x= 14/7 = 2
c) -4X + 6 -10 + 5X = 6X + 9
6 -10 -9 = 6X + 4X - 5X
- 13 = 5X
X = -13/5
2X + 5X = 8 + 5 -7 -6
7X = 0
X = 0/7 = 0
b) 8X -24 + 10 - 2X = - X
7X = 14
x= 14/7 = 2
c) -4X + 6 -10 + 5X = 6X + 9
6 -10 -9 = 6X + 4X - 5X
- 13 = 5X
X = -13/5
Perguntas similares
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás